Tangling with text, hedging with hegemony: spaces, genders and things in African ethnography - Zeitlyn, D (Overseas Publishers Association, 2001)
Examines key issues relevant to spaces, genders and things in the ethnography in Africa. Links between economics, politics and discourse; Study of material culture; Social and cultural traditions and practice.